PREVALENCE OF NASAL CARRIAGE OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS IN A MEDICAL COLLEGE OF INDUSTRIAL AREA OF JHARKHAND - Dwivedi, Roopal; Mukherjee, Sopia; Dash, Chinmaya; Chakraborty, Oindrila (Student’s Journal of Health Research Africa, 2024)
Background Methicillin-resistant Staphylococcus aureus (MRSA) is a significant public health concern due to its ability to cause severe infections and its increasing prevalence in community and healthcare settings. This study aimed to investigate the prevalence of nasal carriage of MRSA in Jharkhand. Understanding the distribution of MRSA carriers is essential for implementing effective infection control measures. Methods A cross-sectional study was conducted involving 130 individuals from various healthcare and community settings in Jharkhand. Nasal swabs were collected and analyzed for the presence of MRSA using standard microbiological techniques. Participants identified as MRSA carriers were treated with 2% Mupirocin Nasal Ointment, and training programs on infection control were conducted for housekeeping and security staff. Results Out of 130 isolates, 6.15% were found to be carriers of Staphylococcus aureus, with 1.53% being MRSA. Among the carriers, 9.2% were doctors and 66.9% were medical students, indicating a higher prevalence in these groups. The study identified that 76.2% of participants had patient contact, highlighting significant transmission risks. The demographics revealed 42.3% male and 57.7% female carriers, with the majority aged under 25. Conclusion The study emphasizes the importance of regular screening and education about MRSA in both healthcare settings and the community. Enhancing awareness and implementing infection control measures are crucial in mitigating the risks associated with MRSA. Recommendation Hospital personnel should be trained on hospital infections, their routes of contamination, and preventive measures for the prevention and control of hospital infections.